Gadd45α modulates aversive learning through post‐transcriptional regulation of memory‐related mRNAs. (4th April 2019) - Aparisi Rey, Alejandro; Karaulanov, Emil; Sharopov, Salim; Arab, Khelifa; Schäfer, Andrea; Gierl, Mathias; Guggenhuber, Stephan; Brandes, Caroline; Pennella, Luigi; Gruhn, Wolfram H; Jelinek, Ruth; Maul, Christina; et al.
Abstract: Learning is essential for survival and is controlled by complex molecular mechanisms including regulation of newly synthesized mRNAs that are required to modify synaptic functions. Despite the well‐known role of RNA‐binding proteins (RBPs) in mRNA functionality, their detailed regulation during memory consolidation is poorly understood. This study focuses on the brain function of the RBP Gadd45α (growth arrest and DNA damage‐inducible protein 45 alpha, encoded by the Gadd45a gene). Here, we find that hippocampal memory and long‐term potentiation are strongly impaired in Gadd45a ‐deficient mice, a phenotype accompanied by reduced levels of memory‐related mRNAs. The majority of the Gadd45α ‐ regulated transcripts show unusually long 3′ untranslated regions (3′UTRs) that are destabilized in Gadd45a ‐deficient mice via a transcription‐independent mechanism, leading to reduced levels of the corresponding proteins in synaptosomes. Moreover, Gadd45α can bind specifically to these memory‐related mRNAs. Our study reveals a new function for extended 3′UTRs in memory consolidation and identifies Gadd45α as a novel regulator of mRNA stability. Synopsis: The RNA‐binding protein Gadd45α controls aversive learning and synaptic plasticity by post‐transcriptional regulation of a set of memory‐related transcripts, containing long 3′UTR extensions. Aversive learning enhances the levels of distinct transcripts, containing long 3′UTR extensions and encoding synaptic plasticity proteins. Gadd45a ‐deficient mice are impaired in the consolidation of hippocampus‐dependent aversive learning and long‐term potentiation. By increasing the stability of such memory‐related mRNAs with extended 3′UTRs, Gadd45α promotes the presence of the corresponding proteins in synaptosomes. The interaction of Gadd45α with these mRNAs is important for its role on memory consolidation. Abstract : The RNA‐binding protein Gadd45α controls aversive learning and synaptic plasticity by post‐transcriptional regulation of a set of memory‐related transcripts, containing long 3′UTR extensions.